2011
DOI: 10.1007/s10876-011-0420-4
|View full text |Cite|
|
Sign up to set email alerts
|

Onset of Amorphous Structure in CaCO3: Geometric and Electronic Structures of (CaCO3) n (n = 2–7) Clusters by Ab Initio Calculations

Abstract: Electronic structures, vibrational analyses, stabilization energies and amorphicity were analyzed for the most stable configurations of the neutral gas phase clusters of calcium carbonate (CaCO 3 ) n (n = 2-7). Minimum-energy structures were generated through simulated annealing using a mix of molecular dynamics/semiempirical optimization and then full optimization at the ab initio level (RHF/6-31G*). HF-level results are calibrated versus MP2/6-31G* results. Though many clusters are symmetric, the structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 24 publications
3
8
1
1
Order By: Relevance
“…The former type of structure has a relatively lower energy (around 0.5 kcal/mol) than the latter. These two configurations seem to be the same as the clusters that have been reported as the stable structure in the gas phase by RosasGarcia et al 19 . The ADDF method can further explore less stable structures, such as Structures 11 and 12.…”
Section: Equilibrium Structures Of Caco3 Dimers and Trimerssupporting
confidence: 84%
See 3 more Smart Citations
“…The former type of structure has a relatively lower energy (around 0.5 kcal/mol) than the latter. These two configurations seem to be the same as the clusters that have been reported as the stable structure in the gas phase by RosasGarcia et al 19 . The ADDF method can further explore less stable structures, such as Structures 11 and 12.…”
Section: Equilibrium Structures Of Caco3 Dimers and Trimerssupporting
confidence: 84%
“…This structural feature leads to the stacking sequence in which Ca ions are aligned by CO3 groups, which can be observed in the tetramer with structure 13. Previously, Roass-García et al has reported that the structure of (CaCO3)n clusters in gas phases is not similar to that of crystalline phases 19 ; however, the structure appearing in the present study is obviously related to the structure of calcite. The present calculation's adoption of the solvent effect may account for these differences.…”
Section: Onset Of the Anhydrous Crystalline Phasecontrasting
confidence: 81%
See 2 more Smart Citations
“…While it is still not clear why PCDA can stabilize such small ACC clusters, the number of CaCO 3 units seven finds support in recent ab initio simulations where the stabilization energy per monomer appears to reach a plateau at this size. [23] Moreover, control experiments with additional ligands ( Figures S2,3) show that besides PCDA, oleic acid and sodium bis(2 ethylhexyl)sulfosuccinate (NaAOT) can stabilize a small amount of clusters. It is speculated that only fatty acids with long alkyl chains and low chain order effectively stabilize the CaCO 3 clusters, especially when we compare the chemical structures of oleic acid and stearic acid which have the same chain length but different degrees of structural saturation.…”
mentioning
confidence: 99%